Association between genetic polymorphisms of MMP8 and the risk of steroid-induced osteonecrosis of the femoral head in the population of northern China. Issue 37 (September 2016) - Du, Jieli; Jin, Tianbo; Cao, Yuju; Chen, Junyu; Guo, Yongchang; Sun, Mingqi; Li, Jian; Zhang, Xiyang; Wang, Guoqiang; Wang, Jianzhong
Abstract: Background: Steroid-induced osteonecrosis of the femoral head (ONFH) is the most common clinical nontraumatic ONFH. Once ONFH occurs, it seriously reduces patients' quality of life. The matrix metalloproteinase/tissue inhibitor of metalloproteinase (MMP/TIMP) system was found to play a significant role in the development of ONFH. The aim of this study was to identify the associations between 7 genes selected from the MMP/TIMP system and steroid-induced ONFH. Methods: We genotyped 34 single-nucleotide polymorphisms (SNPs) of 7 genes selected from the MMP/TIMP system in a case–control study with 285 cases of steroid-induced ONFH and 308 healthy controls. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using the chi-squared test, genetic model analysis, haplotype analysis, and stratification analysis. Results: We found that the minor alleles of rs1940475 and rs11225395 in MMP8 were associated with a 1.32-fold increased risk of steroid-induced ONFH in the allelic model analysis ( P = 0.021 and 0.022, respectively). In the genetic model analysis, we found that rs3740938, rs2012390, rs1940475, and rs11225395 were associated with an increased risk of steroid-induced ONFH. In further stratification analysis, rs3740938 and rs2012390 displayed a significantly increased risk of steroid-induced ONFH in females under the dominant (rs3740938, OR = 2.69, 95% CI: 1.50–4.83, P = 0.001; rs2012390, OR = 2.30, 95% CI: 1.31–4.03, P = 0.012) and additive (rs3740938, OR = 2.02, 95% CI: 1.24–3.29, P = 0.010; rs2012390, OR = 1.77, 95% CI: 1.12–2.80, P = 0.047) models. In addition, haplotype "AGTCA" of MMP8 was found to be associated with a 1.40-fold increased risk of steroid-induced ONFH (95% CI: 1.04–1.88, P = 0.025). Conclusion: Our results verify that genetic variants of MMP8 contribute to steroid-induced ONFH susceptibility in the population of northern China. In addition, we found that gender differences might interact with MMP8 polymorphisms to contribute to the overall susceptibility to steroid-induced ONFH.